Perbandingan Kemampuan Berpikir Tingkat Tinggi Antara Penerapan Model Discovery Learning dengan Memanfaatkan Potensi Ekosistem Pesisir dan Pembelajaran Konvensional pada Siswa Kelas X SMA N 1 Tanjungsari - -, Sulastri -; Indrowati, Meti -; -, Nurmiyati - (Universitas Sebelas Maret Surakarta, 2014)
The purpose of the research was to find out the difference of higher order thinking skills of grade X students after being treated with discovery learningÂ model with employing seashore ecosystem and conventional learning.The research was a quasi experiment with postest only nonequivalent control group design. The population of the research was all student of grade X of SMA N I Tanjungsari, and sample was selected through cluster sampling. Data was collected using test and non-test method. Test method is high order thinking essays, which consisted of analytical thinking skills (C4), evaluate thinking skills (C5), and creative thinking skills (C6). Non-test method was observation and documentation. Hypothesis test used the t-test with SPSS 16 version.The conclusion of the research is there was a difference of higher order thinking skills between application of discovery learning combined with seashore ecosystem and conventional learning of grade X students of SMA N I Tanjungsari. Students of grade X performed best on evaluate thinking skills.Â Â